2009
DOI: 10.1111/j.1440-1827.2009.02475.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent xanthogranulomatous orchiepididymitis and seminoma in the same testis

Abstract: Xanthogranulomatous orchiepididymitis (XGO) is a rare inflammatory and destructive disease of the testis that may simulate testicular malignancy. To the authors' knowledge only 19 cases of XGO have been previously reported. Herein is reported the case of a 52-year-old man with XGO who presented with a left testicular mass and pyogenic discharge from the scrotum. Ultrasound examination indicated heterogeneous testicular areas suggestive of neoplasia. Testicular tumor markers were normal. Orchidectomy was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Differential diagnosis of XGO includes testicular tumor, infectious epididymo-orchitis, malakoplakia, Rosai-Dorfman disease, lepromatous orchitis, and idiopathic granulomatous orchitis. 1 , 7 Malakoplakia is an uncommon granulomatous process of the testis, characterized by accumulation of macrophages with granular and eosinophilic cytoplasm. These macrophages contain characteristic intracytoplasmic inclusions known as Michaelis-Gutmann bodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differential diagnosis of XGO includes testicular tumor, infectious epididymo-orchitis, malakoplakia, Rosai-Dorfman disease, lepromatous orchitis, and idiopathic granulomatous orchitis. 1 , 7 Malakoplakia is an uncommon granulomatous process of the testis, characterized by accumulation of macrophages with granular and eosinophilic cytoplasm. These macrophages contain characteristic intracytoplasmic inclusions known as Michaelis-Gutmann bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Xanthogranulomatous orchitis may coexist with a testicular malignancy. Val-Bernal et al 7 reported a case of XGO and a concurrent, occult typical seminoma. Hence, histopathologic examination is important and is the only conclusive evidence to rule out malignancy and to diagnose xanthogranulomatous inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging findings are mostly non-specific, and differential diagnoses include other infectious, inflammatory and neoplastic diseases of the testes. Moreover, XGO may coexist with testicular malignancies [ 25 ]. Radical orchiectomy can be performed for both definitive diagnosis and curative treatment [ 24 ].…”
Section: Testesmentioning
confidence: 99%
“…Microscopic findings include yellowish nodules with "lipid-laden" macrophages associated to lymphocytes, giant cells and necrosis. However, such findings are not specific to the xanthogranulomatous process and could be concomitant to a tumor (7). The diagnosis is challenging, as the condition can resemble bacterial orchitis, which improves with antibiotic therapy, malakoplakia with typical Michaelis-Gutmann bodies (3) and neoplasm with differences in tumor and immunohistochemical markers (8).…”
Section: Case Presentationmentioning
confidence: 99%